ANALYSIS OF STUDENT WORKSHEETS BASED ON A SCIENTIFIC APPROACH ON NATURAL SCIENCE LEARNING MATERIALS AT SD NEGERI 200303 BARGOTTOPONG - Ummi Yanti Ummi Yanti Harahap; Hasanah (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2021)
This study aims to describe the feasibility of the LKPD (Student Worksheet) based on a scientific approach and the utilization (Student Worksheet) of the scientific-based LKPD. This research was conducted in the fifth grade of SD Negeri 200303 Bargottopong in learning science about natural events. One way that can be used to activate students and provide direct experience to students is by using LKPD (Student Worksheet). This research was conducted using descriptive qualitative research methodology. With the aim of knowing the feasibility and use of LKPD (Learning Worksheets) based on a scientific approach as teaching materials. Based on the results of the study seen from: (1) the suitability of the material with basic competencies showed 100% results, the suitability of the material with the goal shows 100% results, and the suitability of the material with the indicators shows the results of 87.5%. And for the feasibility of the language shows the results of 60% (2) The use of scientific-based LKPD (Student Worksheet) has a very positive effect, so it is feasible to be used in the implementation of learning in class V. In this context the teaching and learning process can generate desire, attraction, improve understanding, and learning outcomes, so that the learning process becomes more effective and efficient.